Transformasi Digital Pada Perbankan Syariah Indonesia: Produk It Dan Jenis Transaksi - Ifa Nurul Islamiah; Nur Nasrina; Nola Fibriyani Bte Salman; Nurul Huda (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2024)
The development of sharia banking in Indonesia has advances in information technology (IT) which have brought significant changes in the way sharia banks offer their products and services. This research discusses sharia banking in Indonesia. This research uses a qualitative study using a liberal research approach by looking for reliable information from written sources, such as books, journals and websites. In the results of this research, E-Banking not only provides comfort but also convenience because the menus on internet banking can be used without having to have special skills, and is safe because internet banking is equipped with a layered security system and is equipped with a token (a tool that issues password numbers). which always changes every time you make a financial transaction). Internet Banking services have many features and provide convenience, comfort and security so that sharia banking services can run easily and efficiently with qualified bank security services, smooth and easy e-banking services are obtained by customers who use e-banking products, in Islamic transactions contain sharia contracts that are applied in the sharia financial institution industry such as: Murabahah Mudharabah, Mudharabah Muqayyadah, Wadiah, Musyarokah, Musyarakah Mutanaqisah, Salam, Istishna, Ijarah, Ijarah Muntahiyah bit Tamlik, Wakalah, Kafalah, hawalah, Rahn, Qordh.